Irenaeus on creation: the cosmic Christ and the saga of redemption - Steenberg, Matthew C. (Vigiliae Christianae, 2008)
Creation and the life of the human race : the contours of Irenaeus' cosmic anthropology -- Comparative sources : the gnostics -- Contemporary Christian sources : Justin and Theophilus Jewish sources -- Creation's stage : the background to Irenaeus' protology the motivation and cause of creation -- Contemporary interpretations of creation and motivation -- Irenaeus on the motivation for creation -- The creator's -- Untrammelled power : a doctrine of creation ex nihilo -- Creation -- Ex nihilo in the broader theological milieu -- Irenaeus' developments creation ex nihilo clarified in Christ -- Chiliasm : reading the beginning through the end and the end through the beginning -- The work of his hands : the creation of the cosmos -- Trinity's creation as an act of Father, Son, and Spirit -- A triune act-three roles in creation -- Distinguishing the creative work -- The 'hands' of the Father -- A 'timeline' of creation -- The days of creation and the beginning of redemption -- Days that lead to growth : 'increase and multiply' -- Recapitulation, and a definition of history -- Dust and life : the creation of the human person -- The triune creation of humanity -- The untilled earth and the constitution of the human person -- the creature wrought of dust and breath : the composition of the human formation -- Four categories of incarnational reading -- God and not angels created the human handiwork -- Christ's birth and human nature -- The material aspect of humanity's being as a creature of flesh -- The human-shaped soul : man's immortal element in relation to the Holy Spirit -- From dust and breath to living image -- The paradise of humankind -- Humanity's relationship to the cosmos -- Humanity's social context : the relationship of Adam and Eve -- History transformed : humanity's transgression -- The tree and the prohibition -- The nature of the prohibition : protection from knowledge misused -- The relationship of knowledge and obedience -- The dynamic of maturing knowledge and responsibility -- A prohibition but not a test -- The fall of knowledge and knowing -- The question of humanity's fall -- The devil and the deception of the human child -- The devil's motivation -- The nature and the accomplishment of the deceit -- The response to sin: humankind -- The opening of humanity's eyes : awareness and reaction -- Humanity's fight and confrontation with God -- The response to sin : God -- The curse -- The clothing and the expulsion from paradise -- Stumbling to perfection : life after Eden -- Cain and Abel, and the internalisation of transgression -- Enoch, Noah and the deluge -- The descendents of Noah and the future of the race -- The Tower of Babel and the distribution of races